Effect of prepregnancy body mass index and gestational weight gain on obstetric and neonatal outcomes A pilot study (Bangladesh Journal of Medical Science, 2011)
Objectives: The study was undertaken to explore the effects of prepregnancy body mass index (BMI) and excess weight gain on maternal and neonatal outcomes different maternal and neonatal outcomes. Methods: Obstetrics records of 496 singleton pregnant women delivered between 2007 and 2009 in IBN SINA Medical College Hospital were reviewed. On the basis of BMI on their first visit the patients were divided into 3 groups; Mat BMI Gr 1, normal (BMI 20–24.9 Kg/m2, n=366), Mat BMI Gr 2, overweight (BMI 25-29.9 Kg/m2, n=102), Mat BMI Gr 3, obese (BMI >30 Kg/m2, n=28). On the basis of gestational weight gain, the subject divided into 2 categories, Gets WtGain Gr A, gestational weight gain 8–15.9 Kg (n=315), Gest WtGain Gr B, gestational weight gain >16 Kg weight gain (n=181). Data were expressed as number (percentage). Proportion test was performed for comparison between two groups. P value